Replacing Imports of Crop Based Commodities by Domestic Production in Finland: Potential to Reduce Virtual Water Imports - Sandström, Vilma; Lehikoinen, Elina; Peltonen-Sainio, Pirjo (Frontiers in Sustainable Food Systems, 2018)
Global water scarcity is a severe threat facing humanity today and it is expected to become even more alarming in the future. Agriculture is the biggest user of freshwater and large volumes of embedded virtual water in food products are traded through the global food system annually. Although Finland has vast water resources, it imports large quantities of virtual water–partly from countries suffering from water scarcity. In this article, we present a novel combination of the virtual water study together with an analysis of the potential reallocation of the outsourced production of rice, soybeans and rapeseed, from the water resource-efficiency point of view. To assess how Finland could reduce the outsourced water consumption by these three crops, we evaluated Finland's potential to replace their imports with local comparable products: domestic barley and oats, field peas and faba beans, and rapeseed, respectively. This replacement would both potentially ease the global pressure on already stressed regions and increase the agricultural diversity of the local agricultural systems. We found that by replacing the imports of the selected crops, considering the realistic potential in Finland, up to 16% of the blue water and almost 30% of the green water embedded in crop imports could be reduced. Although Finland is a minor player in the global food markets, our study presents a highly relevant case of how an industrialized country, with a relatively small population, can contribute to the sustainability of food systems globally.